Chemicals That Disrupt the Endocrine System and Their Effects on Behavior - Yousaf Khan1, Abdul Sattar1, Syed Amin Ullah1, Zia-Ur-Rehman2, Hakimullah3, Madeeha Bibi4, Hina Sarfraz1, Anila Mukhtiar1 (Kashmir Journal of Science)
Endocrine glands are the important glands of humans that perform certain functions and has specific characteristics. The main function of these glands is that they regulate the whole system by producing hormones which they produce indigenously and pour them directly in the blood for a targeted action and all of their functions are involuntary. They are specifically ductless glands and their course of action is regulated by a pea size Pituitary gland or sometimes referred as the Master Gland. Until now, very little has been known about these glands that their actions or functions are being interrupted or disturbed by chemicals or other environmental actions. There are certain chemicals which include chlorpyrifos, DDT, insecticides, pesticides, fungicides and other daily use items such as plastics, paints, furniture, perfumes, toys polishes, electronic gadgets, items of food packaging are reported to have disturbed the normal hormonal functions in humans that are leading to numerous diseases due to either lack of production of specific hormone or increased production of a specific hormone by the action of these chemicals. The diseases that are commonly reported due to the action of the above chemicals and daily use items includes neurological disorders, behavioral disorders, metabolic dysfunction leading to obesity or weakness, thyroid dysfunction, reproductive disturbances and several others that can prove fatal and lead to cancer as well. All these chemicals and items are named as Endocrine Disruptors by the researchers. Still a lot is to be done and there is a huge potential of research in this area which if focused properly can prove as an agent of change in the field of Medical and Health Sciences and Human race can be saved from diverse diseases which may be linked to these disruptors and can be treated timely. In the light of the above, there is dire need of research in this area so as to be familiar to the hazardous and health related issues in Humans caused by these disruptors and to find an alternative for the chemicals and items in order to save the humanity from the negative impacts of these disruptors.